The chief eunuch of the Ottoman harem : from African slave to power-broker - Hathaway, Jane, 1962- (Cambridge : Cambridge University Press, 2018)
Eunuchs were a common feature of pre- and early modern societies that are now poorly understood. Here, Jane Hathaway offers an in-depth study of the chief of the African eunuchs who guarded the harem of the Ottoman Empire. A wide range of primary sources are used to analyze the Chief Eunuch's origins in East Africa and his political, economic, and religious role from the inception of his office in the late sixteenth century through the dismantling of the palace harem in the early twentieth century. Hathaway highlights the origins of the institution and how the role of eunuchs developed in East Africa, as well as exploring the Chief Eunuch's connections to Egypt and Medina. By tracing the evolution of the office, we see how the Chief Eunuch's functions changed in response to transformations in Ottoman society, from the generalized crisis of the seventeenth century to the westernizing reforms of the nineteenth century.
Introducing the Chief Harem Eunuch -- The African connection -- Arrangement in black and white : eunuchs in the Ottoman palace -- The creation of the office of Chief Harem Eunuch and the career of Habeshi Mehmed Agha -- The crisis years of the seventeenth century -- Yusuf Agha and the Koprulu reforms -- A new paradigm : El-Hajj Beshir Agha and his successors -- Exile and the kingdom : the Chief Harem Eunuch and Egypt -- The Chief Harem Eunuch and Ottoman religious and intellectual life -- Reformed out of existence : the denouement of the Chief Harem Eunuch -- Memorializing the Chief Harem Eunuch.
Title from publisher's bibliographic system (viewed on 26 Oct 2018).
Keywords: Eunuchs -- Turkey -- History; East Africans -- Turkey -- History; Harems -- Turkey -- History; Turkey -- History -- Ottoman Empire, 1288-1918.